Interrogating culture: Anthropology, social work, and the concept trade. (July 2021) - Mathias, John; Gulbas, Lauren E; Chin, Matthew; Perry, Tam E
Summary: Interdisciplinary contributions to social work have supported the profession's development as a helping profession. Indeed, drawing from other disciplines has been a way to hone intervention approaches. This article analyzes the history of social work's use of anthropological theory about "culture" in order to critically examine the profession's positioning as a "recipient" of theories. At a time when evidence-based practice is a dominant ideal, this paper offers an opportunity to step back and interrogate a key concept, culture, that is often evoked as interventions are tailored for various populations. Findings: While social work has substantially debated and revised how it approaches culture difference, the core conceptualization of culture as a relatively static set of shared values and traits remains ill-suited to the complex negotiation of diversity in social work practice. The limitations of the culture concept are symptomatic of an exchange relationship with anthropology that positions social work practitioners primarily as recipients of concepts, rather than as interlocutors. Application: By treating intervention as an opportunity for theory revision, anthropologists and social workers can better account for the hybridity, change, and contestation of difference in social work practice. As the social work profession expands globally, a more dialogical engagement with anthropological theories about culture and other key concepts may prove fruitful.